Travels from Dostoevsky's Siberia : encounters with Polish literary exiles - Blake, Elizabeth Ann, 1971- (Studies in comparative literature and intellectual history., 2019)
"Translations in Travels from Dostoevsky's Siberia, gathered from archives and appearing in English for the first time, offer a fresh look at Dostoevsky's House of the Dead from the perspective of his fellow inmates and Siberians who were imprisoned, tortured, and exiled by the regime of Nicholas I. Drawing on archival resources and illustrations, introductory essays immerse the reader in the experience of the political prisoners who must navigate the criminal environment of verbal, physical, and sexual abuse by negotiating with inmates and authorities alike. These eyewitness accounts introduce the reader to Dostoevsky's unfortunates--condemned to share his experience of Russia's carceral system with its interrogations, denunciations, and hostile spaces--whose psychoses become the writer's obsession in his celebrated crime novels"--Publisher.